Contraceptive use and pregnancy rates among women receiving antiretroviral therapy in Malawi: a retrospective cohort study - Hannock Tweya; Caryl Feldacker; Salem Gugsa; Sam Phiri (BMC, 2018)
Abstract Background In 2011, family planning (FP) services were integrated at Martin Preuss Centre (MPC), in urban Lilongwe, Malawi. To date, no previous study evaluated pregnancy rates among HIV-positive women after the integration of FP services into HIV care at the facility. In this study, we investigated whether integration of FP services into HIV clinical care led to increased use of contraceptives and decreased pregnancy rates. Methods This was a retrospective cohort analysis of HIV-positive women from 15 to 49 years of age who accessed antiretroviral therapy (ART) services at MPC. Ascertainment of FP needs, contraceptive methods and pregnancy status were done at ART initiation, and at each ART follow-up visit. Women were offered a wide range of contraceptive methods. Outcomes of interest were contraceptive use and rate of pregnancy. Incident pregnancy was ascertained through patient self-reports during clinic consultation. Trends of contraceptive use and pregnancy rates were analyzed using chi-square (χ2). Results A total of 10,472 women were included in the analysis and contributed 15,700 person-years of observation. Contraceptive use among all women receiving ART increased from 28% in 2012 to 62% in 2016 (p < 0.001). A total of 501 pregnancies occurred, including 13 multiple pregnancies, resulting in an overall pregnancy rates of 3.2 per 100 person-years. Rates of pregnancy decreased from 6.8 per 100 person-years in 2012 to 1.3 per 100 person-years in 2016 (p < 0.001). Conclusion Integration of FP services into HIV care resulted in increased contraceptive use and, subsequently, decreased pregnancy rates in women receiving ART. HIV programs should consider offering FP services to women who are receiving ART.